TOWARDS SAFER JOURNEYS IN CULTURAL HERITAGE TOURISM: EXPLORING THE ROLE OF AI IN TOURISM SAFETY IN SAMARKAND AND BUKHARA, UZBEKISTAN: https://doi.org/10.5281/zenodo.17242596 - Tursunqulov , Inom; Subhadhanuraja , G. (International scientific and practical conference, 2025)
This research explores the integration of Artificial Intelligence (AI) into tourism safety and security in two of Uzbekistan’s most prominent heritage cities, Samarkand and Bukhara. Both cities, located on the historic Silk Road, are UNESCO World Heritage Sites that attract large numbers of international visitors. With rising tourist flows, ensuring visitor safety while preserving cultural assets has become a key priority. The paper examines AI’s role in predictive risk assessment, surveillance enhancement, emergency response, and personalized safety communication in these heritage-rich destinations. By analyzing potential applications such as crowd management at Registan Square in Samarkand, security monitoring at Bukhara’s Ark Fortress, and AI-based health safety during large festivals, the study demonstrates how AI can reinforce tourism resilience. Ethical considerations - including data privacy, surveillance concerns, and cultural preservation - are also discussed. This research contributes to understanding the intersection between advanced technologies and cultural heritage tourism, offering insights for policymakers, destination managers, and technology developers in shaping safer tourism in Uzbekistan.